2009
DOI: 10.1016/j.jtbi.2009.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of heat shock protein synthesis in response to temperature change

Abstract: To cite this version:Zuzanna Szymańska, Maciej Zylicz. Mathematical modeling of heat shock protein synthesis in response to temperature change. Journal of Theoretical Biology, Elsevier, 2009, 259 (3) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable form. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 22 publications
3
54
0
1
Order By: Relevance
“…Furthermore we neglected the impact of ROS and tested the hypothesis that immune responses ensuing heat stroke are mainly mediated by denatured proteins. Denaturation of proteins can occur at temperatures as low as 37-38°C which stimulates the expression of HSPs through activation of HSF-1 (transcription factor of HSPs) [4,13,14]. Peper et al [14] has shown that the denaturation process of proteins is exponential in T c .…”
Section: Framework Modeling and Assumptionsmentioning
confidence: 99%
“…Furthermore we neglected the impact of ROS and tested the hypothesis that immune responses ensuing heat stroke are mainly mediated by denatured proteins. Denaturation of proteins can occur at temperatures as low as 37-38°C which stimulates the expression of HSPs through activation of HSF-1 (transcription factor of HSPs) [4,13,14]. Peper et al [14] has shown that the denaturation process of proteins is exponential in T c .…”
Section: Framework Modeling and Assumptionsmentioning
confidence: 99%
“…We were interested in the hsp70 promoter activity because our molecular construct is a Hsp70-GFP fusion gene transfected in Chinese hamster ovary (CHO) cells, as described in [5]. However, two other architectures from [3,4], use a different input for the temperature stress, an input that was proposed for the first time in a computational network by [1]. It is thus important to compare different heat shock network architectures.…”
Section: Introductionmentioning
confidence: 99%
“…The network from [2] is represented in black, from [3] in red and from [4] in green. HSP:HSF denotes HSP bound to HSF and similar for all other complexes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations